ADVANTAGES OF BIOSTIMULANTS IN GROWING PROMISING PUMPKIN VARIETIES (British Journal of Global Ecology and Sustainable Development, 2022)
This article presents the results of the use of biostimulants "Uchkun", "Gossipren" and "Verva" on the yield of pumpkin variety Spanish 73 and Palov kadu 268 in the Andijan region. It was established that pre-sowing treatment with biostimulants contributed to the enhancement of seed germination and growth processes. The study proved that under the influence of polyprenols contained in the biostimulator "Uchkun", as a result of the complete assimilation of minerals during the germination of pumpkin seeds, the growth and development of the plant is accelerated, resistance to diseases is accelerated and increased.